Một phương pháp xây dựng phần mềm cho hệ vi xử lí ứng dụng thời gian thực - Duc, Dang Van (Journal of Computer Science and Cybernetics, 2018)
This article refers to the software for real-time application system on the basis of microprocessor. The system is devided into task. These tasks are managed by real-time monitor. The real-time monitor is designed so that it had following mechanisms: - Dividing the time of microprocessor - Safeguapding the resources mon – divided - Managing the interruptions The real-time monitor is written by assembler for increasing the speed of the system.